Peningkatan Kemampuan Pemecahan Masalah Matematis Melalui Model Problem Based Learning dengan Menggunakan Soal-soal Berbasis Budaya Lokal - Tensi Olga Vera; Putri Yulia; Nur Rusliah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
The ability to solve problems is part of the purpose of learning mathematics in junior high school, but the reality that occurs in the field is not the case. This can be seen from the lack of trained students and find it difficult to work on the stages of problem solving so that students' mathematical problem-solving abilities are still relatively low. Therefore, Problem Based Learning (PBL) learning model is used by using questions based on local culture. This study aims to look at differences in the improvement of students' mathematical problem-solving abilities between those through the PBL learning model using questions based on local culture and students who use conventional learning in class VII. The method is Quasi Experimental Design with the Random Sampling Cluster technique, VIIB class as the experimental and the VIID class as the control. Data processing is performed by the formula N-gain, then hypothesis testing is done using the t test. From the results of data analysis shows that there are significant differences in the improvement of students' mathematical problem-solving abilities between those who go through the PBL learning model by using questions based on local culture and those using conventional learning.